2017
DOI: 10.1021/acsami.6b12889
|View full text |Cite
|
Sign up to set email alerts
|

Monoolein Cubic Phase Gels and Cubosomes Doped with Magnetic Nanoparticles–Hybrid Materials for Controlled Drug Release

Abstract: Hybrid materials consisting of a monoolein lipidic cubic phase (LCP) incorporating two types of magnetic nanoparticles (NP) were designed as addressable drug delivery systems. The materials, prepared in the form of a gel, were subsequently used as a macroscopic layer modifying an electrode and, after dispersion to nanoscale, as magnetocubosomes. These two LCPs were characterized by small-angle X-ray scattering (SAXS), cross-polarized microscopy, magnetic measurements, and phase diagrams. The magnetic dopants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…More recently additional methods for controlled release have been proposed including magnetic nanoparticles [128] and pH sensitive polymers [129] incorporated into cubosomes.…”
Section: Release Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently additional methods for controlled release have been proposed including magnetic nanoparticles [128] and pH sensitive polymers [129] incorporated into cubosomes.…”
Section: Release Mechanismsmentioning
confidence: 99%
“…The magnetic properties were retained when tested in a magnetic field of a neodymium magnet demonstrating that cubosome systems can be exploited for magnetic drug targeting, hyperthermia treatment, or magnetic resonance imaging. [128] Monoolein cubosomes (stabilized with F127) with 10 wt% of a poly(L-lysine-iso-phthalamide) grafted with L-phenylalanine have been reported. This polymer has a pH responsive hydrophilic/hydrophobic balance changing conformation in response to external pH (extended chains at neutral pH and globular at acidic pH).…”
Section: Release Mechanismsmentioning
confidence: 99%
“…Important examples include nucleic acid loading for gene delivery applications (9,13) and guiding of protein crystallization (14). Other applications, such as directed assembly of hard materials, have been recently proposed as well (15)(16)(17). Restrictions to the use of these lyotropic materials are small unit cells and concomitant narrow water channels (typical diameters, d w = 5 nm) (18).…”
mentioning
confidence: 99%
“…This is interesting because it has been shown that the addition of metal‐based NPs to liquid crystalline particles usually alter their structure. Examples come from reports on cubosomes (dispersions of reverse bicontinuous lipid cubic phases) functionalized with iron oxide NPs and gold nanorods . In both cases, the addition of metal NPs promoted changes in the cell parameter of the initial liquid crystalline structure or favored the formation of additional structures.…”
Section: Resultsmentioning
confidence: 99%